Biopsy quality is essential for preoperative prognostication in oral tongue cancer. Issue 3 (28th December 2020) - Bello, Ibrahim O.; Wennerstrand, Pia M.; Suleymanova, Ilida; Siponen, Maria; Qannam, Ahmed; Nieminen, Pentti; Leivo, Ilmo; Almangush, Alhadi; Salo, Tuula
Abstract : A role for incisional biopsy in preoperative prognostication is increasingly being advocated in oral tongue squamous cell carcinomas (OTSCC). Biopsies at two locations were compared, and prognostic factors in biopsies and their corresponding resections were evaluated. A total of 138 OTSCC biopsy slides from Finland and Saudi Arabia were compared for size (horizontal and vertical) and invasive front. The Finnish cases were assessed for tumor stroma ratio (TSR) and tumor‐infiltrating lymphocytes (TILs) using light microscopy and digital image analysis assessment and compared. Furthermore, TSR, TILs, and previously analyzed budding and depth of invasion (BD) score in biopsies were compared with their evaluation in the corresponding resections. Fifty‐nine percent of Finnish and 42% of Saudi Arabian biopsies were ≥ 5 mm deep, while 98% of Saudi Arabian and 76% of Finnish biopsies were ≥ 5 mm wide. Assessment of invasion front was possible in 72% of Finnish in comparison with 40% of Saudi Arabian biopsies. There was 86.8% agreement between TSR and 75% agreement between TIL evaluation using light microscopy and digital assessment. Significant agreement was obtained on comparing the TSR (p = 0.04) and BD (p < 0.001) values in biopsies and resections. Biopsies of ≥ 5 mm depth from representative OTSCC areas are essential for prognostic information. Clinical pathologists are advised to assess BD score and TSR for prognostic features in such biopsies.